Hubungan kebiasaan sarapan dengan prestasi siswa kelas IV dan V SD - Marlina, Yuliana Eni; Kustiani, Ai; Astuti, Dewi Woro (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Breakfast has a positive relationship with academic achievement, because breakfast activities can directly affect student academic achievement. Skipping breakfast has a bad impact, namely lack of concentration, so that concentration in class is usually lost because the body does not get enough nutrition. Purpose: To determine the relationship between breakfast habits and academic achievement of students in grades IV and V. Method: This study uses an analytical method with a cross-sectional approach. The population in this study were all students in grades IV and V at SDN 01 Astomulyo, Punggur District, Central Lampung Regency with a sample size of 48 people. Data collection tools used observation sheets and questionnaires and were analyzed using chi square. Results: Univariate analysis showed that the majority of respondents were not used to having breakfast as many as 25 (52.1%), 29 respondents (60.4%) had academic achievement in the fairly good category. The results of the bivariate analysis showed that there was a relationship between breakfast habits and academic achievement of students in grades IV and V with a p value = 0.017. Conclusion: There is a relationship between breakfast habits and the academic achievement of students in grades IV and V with a p value = 0.017. Suggestion: Students should maintain good breakfast habits and continue to try to improve them so that their current academic achievement improves.   Keywords: Breakfast; Learning Achievement   Pendahuluan: Sarapan pagi dengan prestasi belajar mempunyai hubungan yang positif, karena kegiatan sarapan pagi dapat mempengaruhi prestasi belajar siswa secara langsung. Meninggalkan sarapan pagi mempunyai dampak yang buruk yaitu kurangnya konsentrasi, sehingga konsentrasi di kelas biasanya terbeli karena tubuh tidak mendapatkan nutrisi yang cukup. Tujuan: Untuk mengetahui hubungan kebiasaan sarapan pagi dengan prestasi belajar siswa Kelas IV dan V . Metode: Penelitian ini menggunakan metode analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh siswa kelas IV dan V di SDN 01 Astomulyo Kecamatan Punggur Kabupaten Lampung Tengah dengan jumlah sampel sebanyak 48 orang. Alat pengumpulan data menggunakan lembar observasi dan lembar angket serta dianalisis menggunakan chi square. Hasil: Analisis univariat diketahui mayoritas responden tidak terbiasa sarapan pagi sebanyak 25 (52.1%), 29 responden (60.4%) prestasi belajarnya berada pada kategori cukup baik. Hasil analisis bivariat menunjukkan bahwa terdapat hubungan antara kebiasaan sarapan dengan prestasi belajar siswa Kelas IV dan V  dengan nilai p = 0.017. Simpulan: Ada hubungan kebiasaan sarapan pagi dengan prestasi belajar siswa kelas IV dan V dengan nilai p-value = 0.017.. Saran: Sebaiknya siswa mempertahankan kebiasaan sarapan yang baik dan terus berusaha meningkatkannya agar prestasi belajarnya saat ini semakin baik.   Kata Kunci: Prestasi Belajar; Sarapan